Reconciling Atmospheric and Oceanic Views of the Transient Climate Response to Emissions. Issue 12 (20th June 2018) - Katavouta, Anna; Williams, Richard G.; Goodwin, Philip; Roussenov, Vassil
Abstract: The Transient Climate Response to Emissions (TCRE), the ratio of surface warming and cumulative carbon emissions, is controlled by a product of thermal and carbon contributions. The carbon contribution involves the airborne fraction and the ratio of ocean saturated and atmospheric carbon inventories, with this ratio controlled by ocean carbonate chemistry. The evolution of the carbon contribution to the TCRE is illustrated in a hierarchy of models: a box model of the atmosphere‐ocean and an Earth system model, both integrated for 1, 000 years, and a suite of Earth system models integrated for 140 years. For all models, there is the same generic carbonate chemistry response: An acidifying ocean during emissions leads to a decrease in the ratio of the ocean saturated and atmospheric carbon inventories and the carbon contribution to the TCRE. Hence, ocean carbonate chemistry is important in controlling the magnitude of the TCRE and its evolution in time. Plain Language Summary: The increase in surface temperature with the amount of carbon emitted to the atmosphere depends on the uptake and storage of heat and carbon. Ocean heat uptake acts to strengthen surface warming, as the ocean becomes more stratified in time. Carbon uptake by the ocean and terrestrial system acts to weaken surface warming by removing carbon from the atmosphere. The proportionality of surface warming to carbon emissions may be written in terms of a thermal contribution multiplied by a carbon contribution. The carbon contribution depends on the increase in the atmospheric carbon inventory plus the maximum amount of carbon that the ocean may hold. To understand the role of ocean chemistry, we diagnose the response of climate models of differing complexity over centennial and millennial timescales. In all the models, there is a similar carbon response: During emissions, the ocean surface acidifies and the maximum amount of carbon that the ocean can hold decreases, which weakens the carbon contribution to the proportionality of surface warming to carbon emissions. Hence, ocean carbonate chemistry is important in controlling the proportionality of surface warming to carbon emissions and its evolution in time. Key Points: Transient Climate Response to Emissions (TCRE) depends on the product of thermal and carbon contributions that need not exactly compensate The carbon contribution to the TCRE depends on the airborne fraction and the ratio of the ocean carbon saturation and atmospheric carbon An acidifying ocean decreases the ratio of ocean carbon saturation and atmospheric carbon and so the carbon contribution to the TCRE